TAOK1 is associated with neurodevelopmental disorder and essential for neuronal maturation and cortical development. Issue 4 (1st March 2021) - van Woerden, Geeske M.; Bos, Melanie; de Konink, Charlotte; Distel, Ben; Avagliano Trezza, Rossella; Shur, Natasha E.; Barañano, Kristin; Mahida, Sonal; Chassevent, Anna; Schreiber, Allison; Erwin, Angelika L.; Gripp, Karen W.; et al.
Abstract: Thousand and one amino‐acid kinase 1 (TAOK1) is a MAP3K protein kinase, regulating different mitogen‐activated protein kinase pathways, thereby modulating a multitude of processes in the cell. Given the recent finding of TAOK1 involvement in neurodevelopmental disorders (NDDs), we investigated the role of TAOK1 in neuronal function and collected a cohort of 23 individuals with mostly de novo variants in TAOK1 to further define the associated NDD. Here, we provide evidence for an important role for TAOK1 in neuronal function, showing that altered TAOK1 expression levels in the embryonic mouse brain affect neural migration in vivo, as well as neuronal maturation in vitro. The molecular spectrum of the identified TAOK1 variants comprises largely truncating and nonsense variants, but also missense variants, for which we provide evidence that they can have a loss of function or dominant‐negative effect on TAOK1, expanding the potential underlying causative mechanisms resulting in NDD. Taken together, our data indicate that TAOK1 activity needs to be properly controlled for normal neuronal function and that TAOK1 dysregulation leads to a neurodevelopmental disorder mainly comprising similar facial features, developmental delay/intellectual disability and/or variable learning or behavioral problems, muscular hypotonia, infant feeding difficulties, and growth problems. Abstract : In this study we expand the cohort of individuals with a neurodevelopmental disorder, carrying a de novo variant in TAOK1 (a), thereby further defining the neurodevelopmental disorder caused by TAOK1 malfunctioning. Using both in vivo (b) and in vitro (c) functional assays, we provide evidence that increased as well as decreased levels of TAOK1 cause disruption of neuronal development, showing that TAOK1 plays an important role in neuronal function. Additionally, our data suggests that both gain of function as well as loss of function mutations are potentially causative for the TAOK1‐related neurodevelopmental disorder.